Influence of Inspiratory Muscle Training on Ventilatory Efficiency and Cycling Performance in Normoxia and Hypoxia - Salazar-Martínez, Eduardo; Gatterer, Hannes; Burtscher, Martin; Naranjo Orellana, José; Santalla, Alfredo (Frontiers in Physiology, 2017)
The aim of this study was to analyse the influence of inspiratory muscle training (IMT) on ventilatory efficiency, in normoxia and hypoxia, and to investigate the relationship between ventilatory efficiency and cycling performance. Sixteen sport students (23.05±4.7 years; 175.11±7.1 cm; 67.0±19.4 kg; 46.4±8.7 ml·kg-1·min-1) were randomly assigned to an inspiratory muscle training group (IMTG) and a control group (CG). The IMTG performed 2 training sessions/day (30 inspiratory breaths, 50% peak inspiratory pressure (Pimax), 5 days/wk, 6-wks. Before and after the training period subjects carried out an incremental exercise test to exhaustion with gas analysis, lung function testing and a cycling time trial test in hypoxia and normoxia. Simulated hypoxia (FiO2=16.45%), significantly altered the ventilatory efficiency response in all subjects (p<0.05). Pimax increased significantly in the IMTG whereas no changes occurred in the CG (time x group, p<0.05). Within group analyses showed that the IMTG improved ventilatory efficiency (VE/VCO2 slope; EqCO2VT2) in hypoxia (p<0.05) and cycling time trial performance (WTTmax(W); WTTmean(W); PTF(W)) (p<0.05) in hypoxia and normoxia. Significant correlations were not found in hypoxia nor normoxia found between ventilatory efficiency parameters (VE/VCO2 slope; LEqCO2; EqCO2VT2) and time trial performance. On the contrary the oxygen uptake efficiency slope (OUES) was highly correlated with cycling time trial performance (r=0.89; r=0.82; p<0.001) under both conditions. Even though no interaction effect was found, the within group analysis may suggest that IMT reduces the negative effects of hypoxia on ventilatory efficiency. In addition, the data suggest that OUES plays an important role in submaximal cycling performance.